Alfabetização científica em nível médio e a preparação dos cidadãos para o processo de tomada de decisões - Rothberg, Danilo [UNESP]; Quinato, Gabriel Augusto Cação [UNESP] (My University, 2011)
The concept of scientific literacy nowadays is permeated by principles eventually inconsistent. Development of cognitive skills, preparation for continuing studies in higher education, preparation for working life and the strengthening of citizenship are some of the competing goals of science education. In respect of Science, Technology, Society and Environment (STSE) Education, the politics of science should be properly taken into account by science education. This paper examines the concept of scientific literacy in the context of STSE Education and points to why and how physics education in high school curriculum should address topics of energy consumption and production in order to provide the background necessary to assess public policies of science, technology and innovation, in particular the Decennial Plan for Expansion of Energy 2020, subjected to public consultation by the Brazilian Ministry of Mines and Energy in 2011.

O conceito de alfabetização científica encontra-se na atualidade permeado por princípios eventualmente incompatíveis entre si. Desenvolvimento de habilidades cognitivas, preparação para a continuidade dos estudos em nível superior, ingresso no mercado de trabalho e formação da cidadania estão entre os objetivos da educação para a ciência, que muitas vezes competem entre si no cotidiano escolar. No contexto das relações CTSA (Ciência, Tecnologia, Sociedade e Ambiente), a dimensão política da ciência deve ser contemplada pelo ensino de ciências. Este artigo revisa o conceito de alfabetização científica no contexto das relações CTSA e caracteriza razões e meios para que o ensino de física em nível médio contemple os conteúdos curriculares sobre consumo e produção de energia, a fim de prover a formação necessária para avaliar políticas públicas de ciência, tecnologia e inovação, em particular o Plano Decenal de Expansão de Energia 2020, posto em consulta pública pelo Ministério de Minas e Energia em 2011.
Scientific literacy in secondary schools and the preparation of citizens for the decision-making process
Keywords: Teaching of Physics; Relations STSR; Scientific literacy; Ensino de física; Relações CTSA; Alfabetização científica